Motherhood Online. - Michelle Moravec (Cambridge Scholars Publishing, 2011)
It may take a village to raise a child, but increasingly that means a virtual village. While the media may focus on the so-called "mommy wars" and babyrazzi follow every move of celebrity moms, millions of mothers world-wide are creating online communities. These mommy groups provide an alternative context for understanding how women construct modern motherhood together. Motherhood Online explores the mutifaceted lives that mom live online. Ranging from longitudinal studies, to focused explor ...